CFD investigation of R134a and propane condensation in square microchannel using VOF model: Parametric study using steady state solution. (1st February 2023) - Alnaimat, Fadi; El Kadi, Khadije; Mathew, Bobby
Highlights: CFD Investigation of flow condensation is carried out on square microchannel. The model is utilized to perform a systematic sensitivity studies. Flow regime transition from film annular, wavy annular, plug, slug flow is observed. The heat transfer coefficient increases with increasing mass flux and inlet vapor quality. Abstract: In this paper, a steady-state analyses of R134a and Propane (R290) condensation inside a 0.5-mm square microchannel are carried out. A three-dimensional (3D) multiphase computational fluid dynamics (CFD) model is developed based on Volume-of fluid (VOF) approach. The model is first validated for mass transfer intensity factor ranging from 60, 000 to 400, 000 s −1 . Thereafter, condensation heat transfer investigation is carried out for different operational conditions including the mass flux ranging from 150 kg/(m 2 ·s) to 1200 kg/(m 2 ·s), saturation-to-wall temperature difference ranging from 5 °C to 25 °C, and inlet vapor quality ranging from 1 to 0.5. The condensation flow regime transition from film annular, wavy annular, plug, slug and fully condensed flow are observed in the obtained simulation results. The average heat transfer coefficient is found to increase with increasing mass flux, low saturation-to-wall temperature difference, and higher inlet vapor quality. In addition, propane is proved to be environmentally friendly substitute of R134a with enhanced heat transfer coefficient by 65–80 % compared to that the latter. The present model allows assessing several two-phase condensing flow parameters with good agreement with literature.